PENTINGNYA MEMAHAMI SEJARAH PERADABAN ISLAM DI INDONESIA - Shofil Fikri; Dwi Putra Arta Sanjaya (STIT Darul Hijrah Martapura, 2022)
The history of Indonesian Islamic civilization began in the 7th century AD. Arab, Persian and Indian traders who traded in the Indonesian archipelago brought Islam there. Although there is no in-depth written evidence of how Islam entered Indonesia, it probably happened gradually through cultural interactions and trade. Ulama play an important role in spreading Islamic teachings in Indonesia. They not only teach religion, but also play an important role in shaping the social and cultural norms of society. The processes of Islamization and acculturation often occur simultaneously, resulting in a special cultural richness in Indonesia. The spread of Islam to Islamic kingdoms, such as the Kingdom of Aceh in Sumatra and the Sultanate of Demak in Java, became the center for the spread of Islam in the surrounding areas. This is an important historical milestone in the spread of Islam in Indonesia. These kingdoms became centers of religion, trade and culture. Islam continued to play an important role in fighting colonialism throughout the colonial period. Islamic values often served as inspiration for anti-colonial movements, and ulama played an important role in leading these movements. Islam's contribution to the formation of the state and society continued to grow after Indonesia's independence in 1945. Until now, Islam remains an integral part of the lives of Indonesian people. The diversity of cultures and ethnicities in Indonesia is reflected in the various Islamic religious practices that exist. Even though Indonesia has a Muslim majority, the values of inter-religious tolerance are also a characteristic of Islamic civilization in this country. The history of Islamic civilization in Indonesia is proof that Islam is able to integrate with local culture, creating harmony in diversity.